1987
DOI: 10.1177/014860718701100101
|View full text |Cite
|
Sign up to set email alerts
|

The effect of route of nutrient administration on the nutritional state, catabolic hormone secretion, and gut mucosal integrity after burn injury

Abstract: So that the efficacy of route of nutrient administration in thermal injury could be determined, a comparison was made between immediate enteral vs parenteral feedings in burned guinea pigs. Thirty-five guinea pigs underwent both catheter gastrostomy and jugular vein catheterization. On postoperative day 8, burned animals [30% total body surface area (TBSA)] were divided into an intragastrically (ig) fed group (N = 14) and a parenterally (iv) fed group (N = 14). Animals in each group received 175 kcal/kg/day wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
7

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(66 citation statements)
references
References 0 publications
1
58
0
7
Order By: Relevance
“…Among the reasons for avoiding the enteral route for nutritional support in the past have been concerns regarding stimulation of an already inflamed pancreas and the belief that successful management of haemodynamic and cardiopulmonary aspects of the patients' care took priority. However, in other conditions characterised by haemodynamic instability and a systemic inflammatory response, early enteral feeding has been shown to attenuate the hypercatabolism associated with thermal injury and sepsis in animals as well as humans [14,15]. The observed benefit in these studies was attributed to preservation of gut barrier function and reduced translocation of viable bacteria and endotoxin into the portal and systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons for avoiding the enteral route for nutritional support in the past have been concerns regarding stimulation of an already inflamed pancreas and the belief that successful management of haemodynamic and cardiopulmonary aspects of the patients' care took priority. However, in other conditions characterised by haemodynamic instability and a systemic inflammatory response, early enteral feeding has been shown to attenuate the hypercatabolism associated with thermal injury and sepsis in animals as well as humans [14,15]. The observed benefit in these studies was attributed to preservation of gut barrier function and reduced translocation of viable bacteria and endotoxin into the portal and systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Essa equação pode ser utilizada em crianças maiores ou adolescentes. A Tabela 1 relaciona os fatores de correção para situações de estresse 4,6 . Necessidades de vitaminas: a oferta basal é essencial para a manutenção das reações metabólicas.…”
Section: Necessidades Nutricionaisunclassified
“…O jejum causa atrofia da mucosa intestinal rompendo a integridade imunológica do trato gastrintestinal e aumentando o risco de translocação bacteriana 4 .…”
Section: Terapia Nutricional Enteralunclassified
See 1 more Smart Citation
“…In addition to these advantages, enteral nutrition during and after certain surgical insults has other benefits including inhibition of energy expenditure [17], the cytokine response [18], the secretion of stress hormones [19], and bacterial translocation [20]. A landmark meta-analysis performed by Moore et al [21] showed that the incidence of infectious and noninfectious complications in trauma patients managed with enteral nutrition was significantly lower than in patients managed with parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%